2001
DOI: 10.1097/00006676-200111000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Successful Subcutaneous Pancreatic Islet Transplantation Using an Angiogenic Growth Factor–Releasing Device

Abstract: This study provides evidence that the subcutaneous tissue is a promising site for pancreatic islet transplantation, which suggests the acceptability of this treatment for diabetic recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 22 publications
1
48
0
Order By: Relevance
“…Nonencapsulated islets may be injected into the liver (4,16,18,19,35,44,50,52) , kidney (5,14,15,16,17,24,27,28,32,34,35,42,46,47) , peritoneal cavity (11,35) , bone marrow (41) and subcutaneous tissue (22,48) . Ikebukuro et al (19) showed that islets and bone marrow cells, when injected into the liver using irradiation as immunosuppression, can increase the functionality of the cells for more than 365 days.…”
Section: Discussionmentioning
confidence: 99%
“…Nonencapsulated islets may be injected into the liver (4,16,18,19,35,44,50,52) , kidney (5,14,15,16,17,24,27,28,32,34,35,42,46,47) , peritoneal cavity (11,35) , bone marrow (41) and subcutaneous tissue (22,48) . Ikebukuro et al (19) showed that islets and bone marrow cells, when injected into the liver using irradiation as immunosuppression, can increase the functionality of the cells for more than 365 days.…”
Section: Discussionmentioning
confidence: 99%
“…Maintained normoglycemia over the long termGu et al (2000)[85] PET mesh bag coated with PVAbFGF in agarose and hyaluronic acidDirect transplantationSubcutaneous tissue of dorsumInduced angiogenesis. Normalized blood glucose levels in the long termKawakami et al (2001)[86] Cationic lipid reagentVEGFDirect transplantationLeft kidney capsuleNormalized blood glucose level. Preserved transplanted islet cells with increasing vascularizationChae et al (2005)[43] R3V6 peptide micellessiRNA-iNOS, 17b-estradiolDirect transplantationLeft kidney capsuleImproved glycemic control.…”
Section: Islet Cell Transplantationmentioning
confidence: 99%
“…Islet cells coated with polyglycolic acid polymer have been shown to provide better glucose tolerance with more revascularization compared with naked islet cells when transplanted into the subcutaneous space of a mouse model of diabetes mellitus [82]. Other studies have reported that bio-artificial materials improved transplanted islet cell survival [8386]. In these studies, a polyethylene terephthalate (PET) mesh bag that enclosed a collagen sponge and biodegradable gelatin microsphere containing basic fibroblast growth factor was transplanted into the subcutaneous space.…”
Section: Islet Cell Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental studies, there are many descriptions of positive data on extrahepatic transplantation sites. The Kyoto and other groups [73] succeeded in achieving normoglycemia in diabetic mice by transplantation of encapsulated islets in muscle, subcutaneous tissue [58,[74][75][76] , renal subcapsule [77] and omentum [56] . These may be candidate transplantation sites in the near future because the loss of islets due to IBMIR, the risk of portal hypertension and portal vein thrombosis could be prevented.…”
Section: Ideal Transplantation Site For Encapsulated Isletsmentioning
confidence: 99%